Development of sugar based biodegradable nanoencapsulators: Understanding the role of the alcohol injection method on the preparation of aqueous dispersions of sorbitan ester vesicles - Alves, Andreia A. S. [UNESP]; Cruz, Pedro F.; Brito, Rui M. M.; Feitosa, Eloi [UNESP]; Antunes, Filipe E. (Elsevier B.V., 2019)
Global environmental concerns on the production, usage and disposal of multiple human-made products have encouraged the study and development of new more ecological materials based on or inspired by biomolecules that may ultimately replace the current existing options. These efforts include the development of sugar-based surfactants. They have been increasingly adopted in selected applications to replace conventional surfactants. Sorbitan ester is a good example of a sugar-based surfactant already in use in the food industry as an emulsifier agent. However, in aqueous solution, the use of this type of surfactants is highly limited as nanocompartments due to their low water solubility. This problem can be overcome by using the alcohol injection method (AIM), where a small amount of alcohol is mixed with the surfactant in water to produce dispersed vesicles. Since the formation of sorbitan ester vesicles are of enormous interest for the nanoencapsulation of active substances for various applications, from food to cosmetics and pharmaceuticals, it is crucial to develop efficient ways to produce these aggregates via the alcohol injection method. The present work reports a study of the role of the alcohol structure on the formation of nanostructures of sorbitan ester. Methanol, ethanol and 2-propanol were selected to evaluate the influence of the alcohol alkyl chain length on the formation and stabilization of the vesicles. Some of the alcohol solutions were evaporated in order to probe the stability of the aggregates even after alcohol removal. Analysis by dynamic light scattering (DLS) and H-1 NMR have shown a direct relation between the size of the alcohol's alkyl chain and the size of the formed sugar-based vesicles. Additionally, it is clear that the alcohol molecules remain in the vesicle, even after the evaporation process. The obtained results demonstrate that it is possible to control the size of the sugar-based sorbitan ester vesicles using the alcohol injection method. Hopefully, this research will encourage and enable the use of nanocompartments in a wider range of applications. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Sugar-based surfactants; Vesides; Biodegradable surfactants; Span; Alcohol injection method